Single-Dose Oritavancin Treatment of Acute Bacterial Skin and Skin Structure Infections: SOLO Trial Efficacy by Eron Severity and Management Setting. Issue 3 (September 2016) - Deck, Daniel; Jordan, Jennifer; Holland, Thomas; Fan, Weihong; Wikler, Matthew; Sulham, Katherine; Ralph Corey, G.
Abstract Introduction Introduction of new antibiotics enabling single-dose administration, such as oritavancin may significantly impact site of care decisions for patients with acute bacterial skin and skin structure infections (ABSSSI). This analysis compared the efficacy of single-dose oritavancin with multiple-dose vancomycin in patients categorized according to disease severity via modified Eron classification and management setting. Methods SOLO I and II were phase 3 studies evaluating single-dose oritavancin versus 7–10 days of vancomycin for treatment of ABSSSI. Patient characteristics were collected at baseline and retrospectively analyzed. Study protocols were amended, allowing outpatient management at the discretion of investigators. In this post hoc analysis, patients were categorized according to a modified Eron severity classification and management setting (outpatient vs. inpatient) and the efficacy compared. Results Overall, 1910 patients in the SOLO trials were categorized into Class I (520, 26.5%), II (790, 40.3%), and III (600, 30.6%). Of the 767 patients (40%) in the SOLO trials who were managed entirely in the outpatient setting 40.3% were categorized as Class II and 30.6% were Class III. Clinical efficacy was similar between oritavancin and vancomycin treatment groups, regardless of severity classification and across inpatient and outpatient settings. Class III patients had lower response rates (oritavancin 73.3%, vancomycin 76.6%) at early clinical evaluation when compared to patients in Class I (82.6%) or II (86.1%); however, clinical cure rates at the post-therapy evaluation were similar for Class III patients (oritavancin 79.8%, vancomycin 79.9%) when compared to Class I and II patients (79.1–85.7%). Conclusion Single-dose oritavancin therapy results in efficacy comparable to multiple-dose vancomycin in patients categorized according to modified Eron disease severity classification regardless of whether management occurred in the inpatient or outpatient setting. Funding The Medicines Company, Parsippany, NJ, USA. Trial registration ClinicalTrials.gov identifiers, NCT01252719 (SOLO I) and NCT01252732 (SOLO II).